Reducing series resistance in Cu2ZnSn(S, Se)4 nanoparticle ink solar cells on flexible molybdenum foil substrates1. Issue 7 (17th January 2018) - Xu, Xinya; Qu, Yongtao; Barrioz, Vincent; Zoppi, Guillaume; Beattie, Neil S.
Abstract : The flexible CZTSSe solar cells on Mo foil achieved efficiency of 3.8%. Abstract : Earth abundant Cu2 ZnSnS4 nanoparticle inks were deposited on molybdenum foil substrates and subsequently converted to high quality thin film Cu2 ZnSn(S, Se)4 photovoltaic absorbers. Integration of these absorbers within a thin film solar cell device structure yields a solar energy conversion efficiency which is comparable to identical devices processed on rigid glass substrates. Importantly, this is only achieved when a thin layer of molybdenum is first applied directly to the foil. The layer limits the formation of a thick Mo(S, Se) x layer resulting in a substantially reduced series resistance.